PENINGKATAN HASIL BELAJAR SISWA KELAS IV PADA MATERI TUMBUHAN SUMBER KEHIDUPAN MELALUI MODEL PEMBELAJARAN PBL - Mochajati; Endang Suprapti; Umi Arsiyati (Universitas Muhammadiyah Surabaya, 2024)
This research was conducted at SD Wali Idris, Tambaksari District, Surabaya City, with the subjects being fourth-grade students. The total number of students was 16, consisting of 10 boys and 6 girls. The object of the research was the teaching of Natural Science with the topic